1997
DOI: 10.1177/039139889702001209
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Methods of Pancreas Islets Immunoisolation

Abstract: The efficacy of two methods of Langerhans islets immunoisolation was compared. For this purpose the function of islets encapsulated with alginate/polyethylenimine/protamine/heparin (APPH) or with alginate/poly-L-lisine/alginate (APA) membranes was assessed: in vitro according to their survival and response to glucose challenges, and in vivo according to their capability to provide sufficient insulin delivery to maintain normal fasting blood glucose following xenotransplantation to streptozotocin diabetic mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…Their identity was confirmed by dithizone staining. One day after isolation the islets cultured at 37°C in a humidified atmosphere of 5% CO 2 were encapsulated by Sun's APA method (2,7). Briefly, handpicked islets were suspended in 1 ml of 1.5% (wt/vol) sodium alginate (Sigma, St. Louis, MO, U.S.A.) and droplets formed by an air‐jet‐syringe pump droplet generator were gelled in 1.1% CaCl 2 solution, exposed successively to 0.05% poly L‐lysine (Sigma) and to 0.15% sodium alginate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their identity was confirmed by dithizone staining. One day after isolation the islets cultured at 37°C in a humidified atmosphere of 5% CO 2 were encapsulated by Sun's APA method (2,7). Briefly, handpicked islets were suspended in 1 ml of 1.5% (wt/vol) sodium alginate (Sigma, St. Louis, MO, U.S.A.) and droplets formed by an air‐jet‐syringe pump droplet generator were gelled in 1.1% CaCl 2 solution, exposed successively to 0.05% poly L‐lysine (Sigma) and to 0.15% sodium alginate.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, alginate gel inside microcapsules was liquefied by 0.05 M sodium citrate. The formed APA microcapsules (7) were spherical and smooth, with reproducible diameters ranging from 500 to 600 microns, and contained one or two islets each. They all exhibited selective permeability, and were impermeable to albumins and globulins, as well as to the cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the increasing morbidity and even mortality brought about by diabetes mellitus, a number of studies have been conducted focusing on engineering pancreatic islets [4749]. We have previously reported that artificial islets can be manufactured from a single cell type, the rat insulin-secreting cell line (RIN-5F), or by coculturing two different cell lines such as RIN-5F and Hep-G2 under shaking mechanism during the culture period [50, 51].…”
Section: Reviewmentioning
confidence: 99%
“…Der [46]. Es bleibt abzuwarten, inwieweit die aktuelle Problematik der Prionen-assoziierten Krankheiten sowie Retrovirus-Infektionen relevant für diese Entwicklung sein wird [55].…”
Section: Zellen Menschlichen Ursprungsunclassified